Figurative Language in Selected Song Lyrics of NIKI’s Nicole Album - Tusino; Puspa Dewi; Sri Maryani (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2026)
Despite the extensive studies on figurative language in song lyrics, limited research has specifically explored emotional functions of figurative language in contemporary pop albums by Asian artists, particularly in NIKI’s Nicole album. This study aims to examine figurative language used in the lyrics of a few of NIKI’s songs from the Nicole album. This study employed a descriptive qualitative method focusing on documents through content analysis. The primary data of this study were a few chosen tracks from NIKI's Nicole album with an emphasis on the lyrics of the songs investigated. To examine the data, the songs were listened to several times, and the lyrics were carefully read to comprehend meanings of the metaphorical language. The data were gathered based on the categories of metaphorical language and categorized for further examination. Findings revealed that eight songs used 75 different types of figurative language which included metaphor as the most frequently used type. The five varieties of figurative language included personification, simile, hyperbole, irony, and metaphor. The use of figurative language created intense emotional expressions which included regret and despair and melancholy. The study demonstrates that song lyrics achieve their highest poetic and beautiful and emotional effects through the use of figurative language which also helps to express the song's main message.